SUSTAINABLE BUSINESS DAN SOCIAL ECONOMIC ENVIRONMENT MASYARAKAT DI PULAU PRAMUKA, KEPULAUAN SERIBU SEBAGAI PERWUJUDAN SMART ISLAND - Elistia, Elistia; Maharani, Novera K.; Afif, Ahmad Sururi (Jurnal Pengabdian Masyarakat AbdiMas, 2019)
AbstractAdministrative District of the Thousand Islands is part of the capital city of the State of DKI Jakarta. The administrative area of the Thousand Islands which is the target partner is the community at Pramuka Island, North Thousand Islands District, Pulau Panggang Village. Through the partnership of the Thousand Islands Family Welfare Development Team (TP PKK) the program was implemented. In order to increase the potential for human resource development this program is aimed at local youth. Character education that has not been maximized, an economy that has not been exploited and is less productive, even though it has good economic potential, such as tourism, small food industries by, the lack of practical skills for the residents of the thousand islands that can improve their welfare in supporting the products of their productive businesses. lack of concern for the community towards the environment. So, from the results of observations, discussions, reviews of relevant data and information, it can be concluded that in the framework of developing community roles, a Community Service Program with the theme of Sustainable Business Education for local superior products and regional Social Environment is needed through model socialization. The Integrated Entrepreneurship Program is supported by community participation for the realization of Smart Island which was held on February 13-14, 2019 at Pramuka Island, Thousand Islands Regency, DKI Jakarta. Keywords: thousand islands, social environment, sustainable business. AbstrakKabupaten Administratif Kepulauan Seribu adalah bagian dari ibukota Negara Indonesia DKI Jakarta. Wilayah administrasi Kepulauan Seribu yang menjadi mitra sasaran adalah masyarakat di Pulau Pramuka, Kecamatan Kepulauan Seribu Utara, Kelurahan Pulau Panggang. Melalui kerjasama mitra Tim Penggerak Pembinaan Kesejahteraan Keluarga (TP PKK) Kepulauan Seribu program ini terlaksana. Dalam rangka meningkatkan potensi pembangunan sumber daya manusia program ini ditujukkan untuk para pemuda/pemudi daerah. Pendidikan karakter yang belum maksimal, perekonomian yang belum tereksploitasi dan kurang produktif, padahal memiliki potensi ekonomi yang baik, seperti pariwisata, industri kecil makanan oleh – oleh, kurangnya keterampilan praktis bagi warga pulau seribu yang dapat meningkatkan kesejahteraanya mendukung hasil – hasil usaha produktif daerahnya, kurangnya kepedulian warga terhadap lingkungan. Jadi, dari hasil observasi, diskusi, tinjauan data dan informasi yang relevan, maka dapat disimpulkan bahwa dalam rangka usaha pengembangan peran masyarakat, maka perlu diselenggarakannya Program Pengabdian kepada Masyarakat yang bertema Edukasi Sustainable Business untuk produk lokal unggulan Pulau dan Social Environment daerah melalui sosialisasi model Program Kewirausahaan Terpadu didukung oleh partisipasi masyarakat untuk perwujudan Smart Island yang di selenggarakan pada Februari 2019 di Pulau Pramuka, Kabupaten Kepulauan Seribu, DKI Jakarta. Kata kunci: kepulauan seribu, social environment, sustainable business